DOES RELATED-PARTY TRANSACTIONS DISCLOSURE AFFECT THE VALUE RELEVANCE OF FINANCIAL STATEMENTS? - Prihastiwi, Diah Agustina; Nugraheni, Agustina Prativi; Pramudyastuti, Octavia Lhaksmi (Jurnal Akuntansi Kontemporer, 2023)
Research Purpose. This study aims to provide support regarding the value relevance of the additional disclosure of RPTs and its predictive value. Research Method. The sample of this research is 343 public companies listed on the Indonesian Stock Exchange from 2016 to 2020. We analyze the effect of RPTs disclosure on the value relevance of financial statement information and its ability to predict abnormal returns using regression analysis between RPTs sales, non-RPTs sales, and total costs with abnormal returns. Research Results and Findings. The analysis results show that the disclosure of RPTs provides incremental information to the users of the financial statement. Furthermore, the disclosure of RPTs also has a significant positive relationship with abnormal returns. These findings show that the provision of information beyond standard requirements is beneficial to financial statement users.